TRANSITION TOWARDS NEW GLOBAL SETTING IN LITHUANIA - Starkevičiūtė, Margarita (Ekonomika, 2011)
The experience gained during the transition decade and five years of the EU membership by Lithuania could be an insightful contribution to an economic policy debate on managing the transition period driven by the global rebalancing of supply and demand.The purpose of the paper is to define the growth enhancing policy measures that have proven efficient during the transition reform period and could be relevant under the new global setting.Findings. Regulated markets set better conditions for the growth of economy than do self-regulated markets, while the most important problem of economic strategy is to evaluate the degree of impact of each determinant on growth and to set their combination favourable for a long-term growth. The growth-enhancing public policy should be aimed to increase the total factor productivity and to ensure competitiveness in global markets.Policy makers have to focus on facilitating an environment conducive to establishing new SMEs in new sectors of economy, instead of focusing on restructuring the old sectors. Restructuring some loss-making industries takes some time, but the efficiency of investments could be ensured if cost reduction is prioritized and leads to an increase in the total factor productivity.